KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU DI SD NEGERI 7 TALANG UBI - Adien, Ria; Amjad, Haidarul; Marlina, Leny; Karolina, Asri (LP2M IAIN Sultan Amai Gorontalo, 2024)
The capacity of the principal in transformational leadership is essential to motivate and improve the professionalism of teachers in the classroom. The purpose of this study is to find out how transformational leadership improves teacher professionalism in SD Negeri 7 Talang Ubi. The principal as a leader plays many roles in the sustainability of the quality of education in schools. In their capacity as educators, teachers play a crucial role in interacting with and serving pupils. Transformational leadership is when a leader is considered to bring solutions to keep up with changing times. Methods used in This research are qualitative by collecting data through several techniques such as interviews, documentation, and field observations the triangulation method in this study. The collected data is then reduced according to the focus of the research, analyzed, and concluded. The principal, vice principal, teachers, and other staff members participated in this study. Current results show that transformational leadership is the most effective characteristic of a leader. By applying transformational leadership values, teachers' motivation to improve competence and professionalism increases by participating in various routine school activities, providing opportunities for teachers to express their opinions and direct teachers in their work positively impacting teacher behaviors.